ROLE OF AUTHENTICITY OF TOURISM TOWARDS PRESERVING THE ROYAL ELEPHANT KRAAL CULTURAL HERITAGE, AYUTTHAYA PROVINCE - Yothicar, Prasert; Sangsawang, Nipaporn (RMUTK Journal of Liberal Arts, 2022)
The purpose of this article is to study the role of the authenticity of tourism in preserving the Royal Elephant Kraal, Ayutthaya Province, to obtain guidance which will be the guidelines to promote the authenticity of tourism in the context of tourism and the preservation of cultural heritage to be sustainable. It can be said that the authentic role of cultural heritage sites affects tourism both positively and negatively. Therefore, to balance the authentic management of cultural heritage sites, it is necessary to consider three dimensions of management: host communities, tourists, and management mechanisms. This will lead to the management of the preservation of cultural heritage authenticity and the development of cultural tourism in an appropriate and sustainable direction.